Pengembangan E-Learning Menggunakan Schoology terintegrasi Model Problem Based Learning Pada Materi Daur Ulang Limbah Untuk SMA: (Development of E-Learning Using Integrated Schoology Model Problem Based Learning in Waste Recycling For High School) - Isnaini Chasanah; Evita Anggereini; Ervan Johan Wicaksana (BIODIK, 2023)
This reseach is to develop, determine the feasibility, and determine the assessment of teachers and students on the product being developed. This type of research is the development of research and development (R&D) with the ADDIE model. The test subjects in this study were a biology teacher and a class X MIPA student at SMAN 6 Batanghari. The data analysis technique in this research is quantitative and qualitative data analysis. The results of media validation by media experts were carried out twice, obtained a score percentage of 87.2% "Very Good" and material validation by material experts was carried out twice, obtained a score percentage of 88.61% "Very Good" The results of teacher assessments obtained a percentage of 83 ,75% "Very Good" While the assessment of small and large groups obtained a percentage score of 88.1% and 89.6% with "Very Good. So it can be concluded that the e-learning product using the developed schoology is very suitable for use in learning biology. abstrak. Penelitian ini bertujuan untuk mengembangkan, mengetahui kelayakan, dan mengetahui penilaian guru dan siswa terhadap produk yang dikembangkan. Jenis penelitian merupakan pengembangan research and development (R&D) dengan model ADDIE. Subjek uji coba pada penelitian ini yaitu satu guru mata pelajaran biologi dan siswa kelas X MIPA SMAN 6 Batanghari. Teknik analisis data dalam penelitian ini adalah analisis data kuantitatif dan kualitatif. Hasil validasi media oleh ahli media dilakukan sebanyak dua kali, diperoleh presentase skor 87,2% â€œSangat Baikâ€ dan validasi materi oleh ahli materi dilakukan sebanyak dua kali, diperoleh presentase skor 88,61% â€œSangat Baikâ€ Hasil penilaiaian guru diperoleh presentase 83,75% â€œSangat Baikâ€ Sedangkan penilaian kelompok kecil dan besar diperoleh presentase skor 88,1% dan 89,6% dengan â€œSangat Baik. Sehingga dapat disimpulkan bahwa produk e-learning menggunakan schoology yang dikembangkan sangat layak digunakan dalam pembelajaran biologi. Kata kunci: E-learning, Schoology, Problem Based Learnig, Daur UlangÂ  Â Limbah